Dystonia in the Mohr-Tranebjaerg syndrome responds to GABAergic substances - Kreisel, Stefan H.; Binder, Johannes; Wöhrle, Johannes C.; Krauss, Joachim K.; Hofmann, Sabine; Bauer, Matthias F.; Hennerici, Michael G.; Bäzner, Hansjörg (Movement disorders, 2004)
Mutations in the X-linked deafness-dystonia peptide 1 (DDP1) gene cause Mohr-Tranebjaerg syndrome (MTS), a rare form of deafness associated with dystonia. In the patient presented here, improvement of dystonic symptoms upon treatment with alcohol and GABAergic substances is demonstrated for the first time.